Answers

The Brainliest Answer!
2014-10-05T13:20:52+05:30
So let the roots be 
a,b

so given 
a + b = 2
and
a³ + b³ = 98
⇒ (a + b)³ - 3ab(a + b) = 98
⇒ 2³ - 3ab × 2 = 98
⇒ -6ab = 90
⇒ ab = - 15

so the required equation = 

x² - (a + b)x + ab = 0

⇒ x² - 2x - 15 = 0       ANSWER

1 5 1
hope it helps
plz mark as best
thank you
2014-10-05T13:22:57+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the roots of quadratic equations are m and n
sum of the roots = 2 : m+n=2
sum of their cubes = 98 : m³+n³=98

(m+n)³ = m³ + n³ + 3mn × (m+n)
⇒2³ = 98 + 3mn(2)
⇒ 8 = 98 + 6 mn
⇒ 6mn = 8-98 =-90
⇒ mn = -90/6 
⇒ mn = -15

We know that for a quadratic equation x²+ax+b = 0,
sum of roots (m+n)= -b/1 = 2  ⇒ a = -2
product of roots(mn) = c/1 = -15  ⇒ b = -15

So equation is x² - 2x -15 = 0

0